Clinical Evaluation of Dibekacin in Urinary Tract Infection in Children - Tambunan, Taralan; Wirya, I. G. N. Wila; Alatas, Husein (Paediatrica Indonesiana, 1982)
Fifty selected cuses of urinary tract infection ( UTI) were treated with Dibekacin with the do~age of 2 mg/kg BW, IM. for seren days. Thirty five cases classified as simple UT 1 and /lie rest fifteen cases as complicured urinary infection. Thirty one cases were injected once a day and the remaining nineteen patients twice a day. The .ciinica!, laboratory und microbiological improvement was 84%, 86% and 62% respectively. Complete improvement was and on 54% cases only. In the group of simple UTI, no significant different result was found on different interval time of drug injection. Similar result was also detected in the group of complicated UTI. The only significant different result was obtained from the cumparison between simple and complicated urinmy infection when the drug was given twice a day, either it was separately assessed clinically, latoratory and microbiologically or combined. Better result was more pronounced in the group of simple UTI but we had to be cautious to interpret this finding. Single daily injection could be reconunended to reduce the dscomfort of parenteral administration.